From Da‘Wah to Economic Empowerment: The Dialectics of Mosque-Based Digital Media Utilization in Strengthening the Community Economy - Alfiera Meutia (Green Publisher Indonesia, 2026)
The Covid-19 pandemic in 2020 brought significant transformations to society’s social, religious, and economic practices, including those within mosque and taklim assembly environments. Restrictions on physical activities during the pandemic triggered a shift in interaction spaces toward the digital realm, particularly through the use of WhatsApp Groups as a primary communication medium. This study aims to analyze the dynamics of WhatsApp Group usage by the Raudhatul Jannah Mosque Taklim Group (MTII) in Taman Nirwana Housing, Bekasi, which developed into a community-based economic transaction space known as Kios Ukhti Taman Nirwana. The research employs a qualitative approach using a case study method. Data were collected through participatory observation, in-depth interviews, and documentation. The analytical framework is based on Georg Wilhelm Friedrich Hegel’s dialectical theory to understand the negotiation process between the sacred values of the da’wah space and the economic needs of the congregation. The findings reveal that mosque-based digital economic practices undergo a dialectical process consisting of thesis (the use of da’wah groups as buying and selling spaces), antithesis (rejection of the perceived shift in sacred functions), and synthesis (the formation of a separate, organized economic space). These results demonstrate that mosques hold strategic potential as centers for community economic empowerment in the digital era, provided they are managed through inclusive, participatory, and religious value–based governance. This study contributes to the scholarly development of da’wah communication, community economics, and the transformation of religious institutions in contemporary society.